Ecological framing of the urban and rural water basins for Environmental Planning - Case of Registro-SP, Brazil - Ajibola Isau Badiru; Maria Aparecida Faustino de Pires (European Regional Science Association (ERSA), 2005)
Considering the physiographic characteristics of Registro-SP, a municipal area situated in the coastal Atlantic region in Brazil. This research has tried to reframe sub-regional water basins for adequate system planning of the urban areas and rural zone. By observing the urban and rural soil use and ocupation interrelated to flood and river areas, five local water basins were identified and investigated for community water basin management. However, urban equipments associated with the natural and human systems were translated into maps and evaluated together with Satellite imagery (Landsat-7UTM RGB-453). Technique has correlated maps for each micro water basin's evaluations focusing on types of natural and artificial sub-systems under landscape analyses of the physical and ecological conditions. A secondary analysis has also characterized the local water basin involved in urban and rural zoning for decision making process (DMP). Synthesis of a general framework associated to sub-regional rivers within the main basin has clearly illustrated different environmental standard for new water management hydrographic unites within the municipal area, as adequate references and suggestions for strategic plan.
Keywords: 330